Finding us - Peterson, Tracie (Peterson, Tracie. Pictures of the heart, 2023)
While taking photographs at an exposition in Seattle in 1909, Camera Girl Eleanor Bennet snaps an image of a woman in widow's clothes with deep sorrow etched in her expression and a young infant in her arms. Planning to study botany at the University of Washington, Eleanor becomes friends with botanist Bill Reed. When she shows him the photograph of the widow, Bill recognizes the woman as the sister-in-law he believed lost in a shipwreck. As they hunt for the woman-- Amelia Reed-- to reunite her with her grief-stricken husband, they must learn to trust that God will direct their paths. -- adapted from back cover